Fibromyalgia Syndrome: A Case Report on Controlled Remission of Symptoms by a Dietary Strategy - Lattanzio, Silvia Maria; Imbesi, Francesca (Frontiers in Medicine, 2018)
A 34-years-old woman suffered from significant chronic pain, depression, non-restorative sleep, chronic fatigue, severe morning stiffness, leg cramps, irritable bowel syndrome, hypersensitivity to cold, concentration difficulties and forgetfulness. Blood tests were negative for rheumatic disorders. The patient was diagnosed with Fibromyalgia Syndrome (FMS). Due to the lack of effectiveness of pharmacological therapies in FMS, she approached a novel metabolic proposal for the symptomatic remission in FMS. Its core idea is supporting serotonin synthesis by allowing a proper absorption of tryptophan assumed with food, while avoiding, or at least minimizing the presence of interfering non-absorbed molecules such as fructose and sorbitol. Such a strategy resulted in a rapidimprovement of symptoms after only few days of diet, and a full recovery from most of the symptoms occured in 2 months. Depression, widespread chronic pain, chronic fatigue, non-restorative sleep, morning stiffness, and the majority of the comorbidities remitted. Energy and vitality were recovered by the patient as prior to the onset of the disease, reverting the occupational and social disabilities. The patient episodically challenged herself breaking the dietary protocol, leading to its negative test and to the evaluation of its benefit. These breaks correlated with the recurrence of the symptoms, supporting the correctness of the biochemical hypothesis underlying the diet design toward remission of symptoms but not as a final cure. We propose this as a low-risk and accessible therapeutic protocol for the symptomatic remission in FMS, with virtually no costs other than those related to vitamin and mineral salt supplements in case of deficiencies. A pilot study is required to further ground this metabolic approach to FMS, and to finally evaluate its inclusion in the guidelines for clinical management.